Guia de Procedimientos Contables y Tributarios para las Empresas Comercializadoras de Productos de Primera Necesidad de la Ciudad de Loja - Chillogallo Malacatus, Rosa Alba (2017)
With this background, we designed a Guide to Accounting, Tax Procedures appropriate to the needs of companies, clearly establishing the different accounting processes, and tax in this way reduce the occurrence of errors, fraud to safeguard the assets of companies. Consequently, and in order to comply with the main objective, it was based on the specific objectives within which the first one refers to the design of accounting and tax procedures for the trading companies of the City of Loja in order to help facilitate better control of Business. The second objective is to develop procedures focused on tax obligations such as tax returns, withholding taxes, withholding VAT, registration of ruc, form, in order to verify if they fully comply with their tax obligations. For the fulfillment of the third objective, the flowcharts of both the accounting and tax processes were designed with the purpose of informing the owners of 6 the companies about the results obtained from the preparation of a guide to tax accounting procedures. This will allow companies to have a valuable tool for obtaining real and timely information to achieve efficient and effective management. The methodology and information gathered from different computer sources were constituted as basic tools for the practical and representative theoretical execution of the present dissertation work and thus to establish alternatives focused on the guides of accounting and tax procedures of the trading companies of the City of Store. With the development of the tax accounting guide, it was possible to contribute with a contribution to the companies so that the work is a support instrument to help them to know with certainty the economic movement in which their company is.